Ferrite nano fill catalyst clay pellet production - Tosun, Yıldırım İsmail (STEF92 TECHNOLOGY LTD, 2015)
Magnetic nano-ferrite magnetic recording materials, biomedical, catalysts, are finding a variety of application areas including. Bil?e? different ferrite and those qualities are studied by many researchers. The physical properties of Nanoferrit differs from other nanomaterials. Superconductivity, magnetism semiconducting magnetic waves fighting cancerous cells diagnosis, various functions, such as improving blood flow can be realized. Our country is also necessary to revive this sector. Nano-sized spinel ferrite M, a divalent atom znfe2o4 manner, a face-centered cubic (FCC) lattice with a unit. Buildings, metal cations, i.e., tetrahedral (A) and octahedral sites (B) includes two surfaces formed by the site. This produces a different local symmetry. Octahedral net magnetization in the cage and the fraction of divalent ions in the octahedral sites in the tetrahedral cationic dispersion plane depends on the cationic dispersion. An ion anisotropy of a specific ion in the same manner generates a magnetic anisotropy. Hard magnetic materials for applications such as Zn ferrite magnetization long-term storage is very convenient. These results are characterized by a high cubic anisotropy magnetocrystall. Zn ferrite system fully ferrite magnetic properties znxfe3-xo4 reverse parameter in octahedral sites and Fe3 + ' s can be adjusted with relative existence and effect of microwave Microwave interactive oleic asit dissolved 20-45 nm in size are produced in ferrite nano materials by heating and grinding, the change in the nature of the impact of the product was determined the effect of microwave magnetic susceptibility and catalysis.
Keywords: Nanotechnology; Magnetic nano; Ferrite catalysis; Micro zinc ferrites